Case Report: Response With Immunotherapy in a Patient With Mixed Neuroendocrine Non-Neuroendocrine Neoplasms of the Gallbladder - Liu, Chao; Hua, Xiangwei; Yang, Zhen; Guo, Yuan; Wu, Liqun; Cai, Jinzhen; Li, Ling; Zhang, Yaxuan; Fan, Ning (Frontiers in Oncology, 2021)
Background: Primary neuroendocrine tumors of the gallbladder (GB-NETs) are rare, accounting for 2% of all gallbladder cancers. Among GB-NETs, mixed neuroendocrine–non-neuroendocrine neoplasms of the gallbladder (GB-MiNENs) are sporadic. Case Presentation: A 56-year-old woman admitted to our hospital due to right upper abdominal pain of 3 days duration. She underwent positron emission tomography/computed tomography, which showed multiple metastatic tumors and was unsuitable for operation. Initially, the patient diagnosed with gallbladder adenocarcinoma. She underwent PD-1 inhibitor or combined with chemotherapy considering the PD-L1 high positive score. In the latter, the patient has the opportunity of surgery, and the new diagnosis was MiNENs. She achieved long-term disease control and survived for nine months from the first diagnosis. Conclusion: This case might support the strategy that PD-1 inhibitor could provide a feasible treatment option for MINENs of gallbladder patients with the positive expression of PD-L1 in the future.